Selection of pepper genotypes for ornamentation based on ideotype (Research, Society and Development, 2020)
Peppers of the Capsicum annuum species are the most suitable for use in ornamentation, for having characters that confer aesthetic value, for being easy to cultivate and for good adaptability in pot. Despite the great variability that exists, in Brazil few commercial varieties are used for this purpose. It is of interest to the plant breeder, an ideotype that contains all the characteristics of interest for commercialization. The aim of the present study is to evaluate and select C. annuum genotypes, with potential for ornamentation that most closely resemble the proposed ideotype. 14 quantitative traits and seven qualitative traits were evaluated in 29 C. annuum genotypes, in a completely randomized design with five replications. The cultivar Calypso was used as an ideotype for presenting desirable characters to the ornamental pepper market. Nine genotypes were selected as the most similar to the Calypso ideotype (ideotype), with the potential to be used in future crossings between them and / or with the ideotype.